2017
DOI: 10.1016/j.jacc.2017.05.020
|View full text |Cite
|
Sign up to set email alerts
|

β 1 -Blockade Prevents Post-Ischemic Myocardial Decompensation Via β 3 AR-Dependent Protective Sphingosine-1 Phosphate Signaling

Abstract: Background Although β-blockers increase survival in patients with heart failure (HF), the mechanisms behind this protection are not fully understood, and not all patients with HF respond favorably to them. We recently demonstrated that, in cardiomyocytes, a reciprocal down-regulation occurs between β1-adrenergic receptors (ARs) and the cardioprotective sphingosine-1-phosphate (S1P) receptor-1 (S1PR1). Objectives The authors hypothesized that, in addition to salutary actions due to direct β1AR-blockade, agent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 28 publications
4
47
0
Order By: Relevance
“…Evidence for β3-AR/S1P cross-talk have been recently reported and this molecular interplay seems to be involved in physiopathological effects in different cellular contexts [30,46]. The occurrence of functional interplay between β3-AR and SK/S1P axis has been demonstrated by both pharmacological and RNA interference approach, and these results were further confirmed by the employment of a specific β3-AR agonist.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Evidence for β3-AR/S1P cross-talk have been recently reported and this molecular interplay seems to be involved in physiopathological effects in different cellular contexts [30,46]. The occurrence of functional interplay between β3-AR and SK/S1P axis has been demonstrated by both pharmacological and RNA interference approach, and these results were further confirmed by the employment of a specific β3-AR agonist.…”
Section: Discussionmentioning
confidence: 79%
“…Literature data showed that S1P signaling strongly affects NB progression [27,29]. Notably, a recent paper reported a cross talk between the β3-AR and the S1P signaling in heart failure [30]. In view of this experimental data, we wondered whether these two pathways were potentially related in NB tumor biology.…”
Section: β3-ar Blockade Modulates S1p Metabolism and Signaling In Hummentioning
confidence: 92%
“…The S1PQ1 group had higher LVEDV than S1PQ2 group (230.46 (SD 83.55) vs 187.76 (SD 65.60), P=0.007). And Cannavo A et al [5] showed a mutual regulation mechanism between S1P/S1PR function and βadrenergic receptor function. These results suggest that an abnormal decline of plasma S1P may be associated with heavier ventricular remodelling.…”
Section: U-shaped Relationship Bridges the Gap Between Different Mechmentioning
confidence: 99%
“…In the model of post-ischemic HF, Cannavo A et al demonstrated that either cardiac or circulating levels of S1P are reduced compared to nonischemic control [6]. S1PR1 receptor expression decreased after myocardial infarction, and chronic S1P treatment could arrest post-MI HF progression [5]. Meanwhile, S1P lyase activation in the myocardium following ischemia leads to reduced S1P levels and that knockout mice for this enzyme exhibit higher S1P levels and smaller infarct size [18].…”
Section: U-shaped Relationship Bridges the Gap From Basic Study To CLmentioning
confidence: 99%
See 1 more Smart Citation